Water Quality Map Extraction from Field Measurements Targetting Robotic Simulations. Issue 5 (2022) - Anderson, A.; Martin, J.G.; Mougin, J.; Bouraqadi, N.; Duviella, E.; Etienne, L.; Fabresse, L.; Langueh, K.; Lozenguez, G.; Alary, C.; Billon, G.; Superville, P.J.; et al.
Abstract: The assessment of the quality of water can be shortly defined as the analysis of its physical, chemical and biological characteristics in order to determine the degradation of freshwater resources. In this context, one of the latest technological methods for real-time data acquisition comes from the use of unmanned vehicles (aerial, surface and underwater). Therefore, the development of control strategies to perform environmental missions is crucial to manage water resources in an efficient and effective way. Prior to the actual implementation, some in-silico experiments are needed to test the proposals, which is one of the purposes of this work. This proposal, based on real experiments in a lake, presents a novel method for the construction of a water quality map based on polygons. The result is compared with a classical data generation method showing positive outcomes. The generated limnological map has a twofold purpose: to test set-based predictive controllers in simulation scenarios with an aquatic robot and to determine if there is a source of contamination in the analyzed region of the lake.